Analisis Dampak Ekonomi dan Strategi Mengatasi Pengangguran Akibat Covid-19 - Ahmad Hasibuan, Nur Fadhilah (CV. Pusdikra Mitra Jaya, 2024)
The Covid19 outbreak has had an overall effect on all sectors of life, especially the economic sector. This study aims to analyze the impact and strategies in overcoming rising unemployment during the covid19 period. This study uses a qualitative method, namely a literature study, studies obtained from relevant literature and news related to the unemployment rate during the Covid-19 period. The results of this study indicate that the Covid-19 pandemic has had a significant impact on increasing unemployment and strategies for dealing with unemployment are carried out by the government and individuals.